The auto/biographical discourse of the novel “A Dead Man in Deptford” by Anthony Burgess - Бусел, Анна Павловна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article deals with the specifics of auto/biographical field of the novel “A Dead Man in Deptford” by E. Burgess. It is emphasized that the author’s expressive subjectivity influenced problematic, characters and originality of the plot and compositional organization of the biographical novel “A Dead Man in Deptford”. There is an overlap between the two discourses in the text – the life and work of both the author and the main character of the novel. Biographical facts as well as literary texts by Ch. Marlowe were used as an ideologic conception of the novel and the novel makes it possible to interpret the life and work of not only the protagonist but also its author – E. Burgess.